Design of reflectarray antenna using different unit cell element at Ku-band - Uwizeye, Christelle (2016)
Reflectarray antenna offers several advantages over parabolic and phased array antennas, such as low weight, low profile, low cost, small size and low transmission losses due to the feeding mechanism. However, reflectarray antennas require the use of element shapes which are able to meet the requirements of modern technologies. This has led to the use of several unit cell designs by different researchers. However there is no specific shape which meets all specifications and design requirements. Therefore is a need to investigate several element shapes in the unit cell design to provide a quick reference guide for researchers. In this project, six different unit cells which are rectangular, circular, triangle, ring, rectangular with slot and cross shapes at 12 GHz are investigated through simulation. Each of the shape is then used in the complete antenna design of 11x11 reflectarray elements fed by a center feed horn antenna. The antenna results shows circular shapes gives the best performances with higher gain of 20:6 dB and low side lobes level in E and H planes. The outcome of this study provide insight in the development of high performance antenna.